Biomechanical comparison of intramedullary nail and plate osteosynthesis for extra-articular proximal tibial fractures with segmental bone defect - Gao, Weihang; Zhao, Ke; Guo, Yuanyuan; Xie, Mao; Feng, Xiaobo; Liu, Ping; Xie, Xin; Fu, Dehao (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: Proximal tibial fractures are common, but the current available internal fixation strategies remain debatable, especially for comminuted fractures. This study aimed to compare the biomechanical stability of three internal fixation strategies for extra-articular comminuted proximal tibial fractures. Methods: A total of 90 synthetic tibiae models of simulated proximal tibial fractures with segmental bone defects were randomly divided into three groups: single lateral plating (LP), double plating (DP) and intramedullary nailing (IN). Based on the different number of fixed screws, the above three groups were further divided into nine subgroups and subjected to axial compression, cyclic loading and static torsional testing. Results: The subgroup of intramedullary nailing with five proximal interlocking screws showed the highest axial stiffness of 384.36 ± 35.00 N/mm. The LP group obtained the lowest axial stiffness performance with a value of 96.59 ± 16.14 N/mm. As expected, the DP group offered significantly greater biomechanical stability than the LP group, with mean static axial stiffness and mean torque increasing by approximately 200% and 50%, respectively. According to static torsional experiments, the maximum torque of the DP subgroup was 3308.32 ± 286.21 N mm, which outperformed all other groups in terms of torsional characteristics. Conclusion: Utilizing more than four distal screws did not provide improved biomechanical stability in the LP or DP groups, while a substantial increase in the biomechanical stability of DP was obtained when an additional medial plate was used. For the intramedullary nailing group, increasing the number of proximal interlocking screws could significantly improve biomechanical stability, and the intramedullary nailing with three proximal interlocking screws had similar static and cyclic stiffness as the DP group. The intramedullary nailing with five proximal screws had better axial stability, whereas DP had better torsional stability.